A inserção de novas tecnologias em conjunto com atividades experimentais no ensino de física - Libardoni, Gláucio Carlos (2012)
We present a pedagogical a proposal for inclusion of Information and Communication Technologies (ICTs) in teaching Physics in High Scholl for the automatic acquisition of experimental data and numerical and graphical analysis of physical phenomena. This pedagogical proposal was implemented in a number of educational activities we have developed and applied in the study of a simple pendulum, damped pendulum, uniform rectilinear motion (MRU) and uniformly varied rectilinear motion (MRUV) in two schools (public and private) from Santa Maria / RS / Brazil in the years 2010 and 2011. In the development of program content of experimental data acquisitions were made through filming, using low-resolution digital cameras (eg, those available on mobile phones). The numerical and graphical free analyzes of data were made using the OCTAVE (a mathematical software compatible with MATLAB). The use of these resources in the classroom and extracurricular schedules provided a quantitative study of phenomena in parallel to promote a range of computing students during the construction of knowledge. These results show that ICTs have played a key role in the progress of educational activities, as promoted active participation of students in teaching / learning process.